2015
DOI: 10.1016/j.brainres.2015.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Audio–visual integration through the parallel visual pathways

Abstract: Audio-visual integration has been shown to be present in a wide range of different conditions, some of which are processed through the dorsal, and others through the ventral visual pathway. Whereas neuroimaging studies have revealed integration-related activity in the brain, there has been no imaging study of the possible role of segregated visual streams in audio-visual integration. We set out to determine how the different visual pathways participate in this communication. We investigated how audio-visual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Paraskevopoulos et al 2015). However, in musically lay individuals, prior studies have indicated that the likelihood of perceiving the double-flash illusion is highly correlated with white matter connectivity between occipito-parietal regions, the putative ventral/dorsal streams comprising the "what/where" pathways (Kaposvari et al 2015). This suggests that parallel visual channels play an important role in audiovisual interactions and the temporal binding of disparate cues as required by double-flash percepts (Shams et al 2000(Shams et al , 2002.…”
Section: Experience-dependent Changes In Multisensory Perceptionmentioning
confidence: 99%
“…Paraskevopoulos et al 2015). However, in musically lay individuals, prior studies have indicated that the likelihood of perceiving the double-flash illusion is highly correlated with white matter connectivity between occipito-parietal regions, the putative ventral/dorsal streams comprising the "what/where" pathways (Kaposvari et al 2015). This suggests that parallel visual channels play an important role in audiovisual interactions and the temporal binding of disparate cues as required by double-flash percepts (Shams et al 2000(Shams et al , 2002.…”
Section: Experience-dependent Changes In Multisensory Perceptionmentioning
confidence: 99%
“…The rate of visuo-motor adaptation was related to the microstructure of the superior cerebellar peduncle, a structure containing fibres connecting the cerebellum and premotor cortex [65]. We showed that audio-visual integration correlates with the microstructural integrity of fibres in the ‘where’ and ‘what’ visual pathways in low and high contrast conditions respectively [45]. Motion detection threshold was found to be correlated with the diffusion properties of the fibres connecting frontal and parietal association areas, putative attention related regions [44].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that correlation between the individual structural variability and behavioural performance can identify the involved neuroanatomical structures [42]. The microstructural integrity of the white matter as defined by diffusion tensor imaging is capable of revealing the coupling of structure and function [4345]. Accordingly, Thiebaut de Schotten showed that the relative size of the right superior longitudinal fasciculus is correlated with the behavioural bias on the line-bisection task [46], which results were later replicated by Cazzoli and colleagues [47].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work examining the ventral and dorsal visual streams in auditory/visual integration suggest that both parallel visual pathways may play a role in the auditory/visual interaction (Kaposvari et al, 2015); however most studies have reported a specific dorsal visual stream deficit in SP (e.g. Butler and Javitt, 2005).…”
Section: Discussionmentioning
confidence: 99%